Pelatihan Penggunaan Alat Bantu Kebersihan Mulut untuk Pencegahan Penyakit Periodontal pada Kader Kesehatan Sendangmulyo, Semarang: Training on the Use of Oral Hygiene Aids for the Prevention of Periodontal Disease for Health Cadres in Sendangmulyo, Semarang - Steffi Triany Arnov; Risyandi Anwar; Lira Wiet Jayanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Periodontal disease is a chronic infection that can damage the supporting tissues of the teeth, leading to tooth mobility, with high prevalence worldwide. Efforts to prevent periodontal disease can be carried out through comprehensive dental and oral hygiene. Using oral hygiene aids other than toothbrushes can reduce the risk of developing periodontal disease. The purpose of this community service activity is to provide solutions to community problems, particularly those related to maintaining oral hygiene and health. This event was attended by 40 health cadres from the Sendangmulyo sub-district in Semarang. The training began with a pre-test, a brief education on the types and use of oral hygiene aids. Participants were then divided into small groups for hands-on practice, assisted by tutors for each group. The training concluded with a post-test. The hands-on practice method helped the cadres gain a better understanding of how to use various types of oral hygiene tools. The small-group tutorial method also facilitated the transfer of knowledge and proper technique. The results showed that this activity provided knowledge and improved the skills of health cadres in using oral hygiene aids other than toothbrushes. It is hoped that the cadres can share this knowledge with the community.